THE INFLUENCE OF WORKLOAD, WORK MOTIVATION, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Purwanto, Sofia Rizky; Meilani, Yohana F. C. P. (Transpublika Publisher, 2024)
The objective of this research is to explore how the performance of employees at PT. XYZ is influenced by their workload, motivation, and the environment in which they work. This research utilises quantitative methods by administering surveys to employees across different sectors, with a total of 108 participants. The gathered information was analysed using model assessment and structural equation modelling through SmartPLS 4.1.0.2. According to the data analysis, the performance of employees at PT. XYZ is influenced by the amount of work they have, their motivation levels, and the environment they work in. The findings suggest that motivation and work environment play a crucial role in enhancing employee performance, whereas workload does not seem to have a significant detrimental impact. The results of this research can offer important perspectives, proof, and understanding to scholars and personnel managers. Organizations can establish a strong workforce that helps achieve the best organizational objectives by introducing methods to supervise workload, boost work drive, and enhance the work atmosphere. It is recommended that personnel managers create guidelines concentrating on controlling workload, hiring, education, drive, and enhancing possibilities while promoting a forward-thinking attitude among workers. These measures will promote creativity, cognitive flexibility, punctuality, and enhance worker effectiveness and results.